A Map of Days : a novel - Riggs, Ransom (New York, NY : Dutton Books, 2018)
"After having saved the peculiar world, Jacob Portman is back in Florida with his peculiar friends, where they set out on a journey across America to discover the truth about Jacob's grandfather"--
Keywords: Supernatural -- Fiction; Voyages and travels -- Fiction; Grandfathers -- Fiction